Ethnobotanical indices on wound healing medicinal plants in the Arjuna River of Virudhunagar District in Tamil Nadu, Southern India (Asian Journal of Ethnobiology, 2021)
Abstract. Shanmugam S, Rajagopal V, Balamurugan S, Muthupandi CP, Eswaran VM, Raveendraretnam K, Rajendran K. 2021. Ethnobotanical indices on wound healing medicinal plants in the Arjuna River of Virudhunagar District in Tamil Nadu, Southern India. Asian J Ethnobiol 4: 31-36. Medicinal plants can perform a significant role in preventing pathogenic attacks in the body. Plants are a great source of primary health care due to certain chemical compounds. Research on the traditional knowledge related to plants used for wound healing still needs adequate attention. The present study was carried out to document the therapeutic uses of medicinal plants in the Arjuna Riverbank of Virudhunagar District in Tamil Nadu to heal various wounds. The frequent fieldwork was conducted from June 2018 to March 2019 in four villages selected for this study. The scientific name, family name, local name (in Tamil), part (s) used, mode of preparation, method of application, and medicine administration were recorded. The ethnomedicinal data were statistically analyzed by ethnobotanical indices such as Use Value (UV), Citation Frequency (CF), and Relative Importance (RI). A total of 23 medicinal remedies prepared from 23 plants were recorded. Mimosa pudica was found with the highest values in all three indices. Further research on the phytochemistry and pharmacology of these medicinal plants should be conducted.
Keywords: Arjuna river, Ethnobotanical Indices, Medicinal plants, Wound heal